Implementasi Etika Bisnis Islam Pada Reseller Anna Collection Di Pagesangan Surabaya - Sasa Putri, Dahlia Kumara; Suryaningsih, Sri Abidah (Jurnal Ekonomika dan Bisnis Islam, 2019)
Business ethics is an activity that makes behavior better in doing business or trading so that customers feel satisfied without feeling aggrieved. The purpose of this study was to find out Islamic business ethics conducted by “Anna Collection” reseller in Pagesangan Surabaya. This research is the kind of case study research by the method of survey. Research conducted in the form of a descriptive study using literarure as well as take primary data in the form of filling the questionnaires and interviews. There are several indicators that can be used to measure Islamic business ethics, including five principles, namely unity, balance, free will, responsibility, and truth (honesty). The respondent in this research is the “Anna Collection” reseller in Pagesangan Surabaya.